2021
DOI: 10.1088/1755-1315/648/1/012118
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to climate change by using drought tolerant and early maturing rice varieties in Majalengka Regency

Abstract: One of the efforts to anticipate the impact of climate change on rice is the introduction of new high yielding and early maturing varieties tolerant drought. The aim of this study was to examine the growth performance and potential production of several early maturing and drought tolerant rice varieties in lowland on dry season. The assessment was conducted in Majalengka regency from June to September 2019. Five varieties used were Inpari 39, Cakrabuana, Inpago 11, Rindang 1, and Luhur 1 with through applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Some of them are Inpari 38, with an age of 105 DAS, Inpari 39, with a period of 115 DAS and Inpari 41, with an age of 114 DAS (Ministry of Agriculture, 2022). Noviana et al (2021) reported that Inpari 39, Cakrabuana, Inpago 11, Rindang 1 and Luhur 1 have the potential to experience drought stress during the dry season on rainfed paddy fields with average productivity of 6 to 7 t ha -1 . Further, Cakrabuana has the highest grain yield around 7.15 t ha -1 when matured at 85 days after planting.…”
Section: Using Short-lived Paddy Varietiesmentioning
confidence: 99%
“…Some of them are Inpari 38, with an age of 105 DAS, Inpari 39, with a period of 115 DAS and Inpari 41, with an age of 114 DAS (Ministry of Agriculture, 2022). Noviana et al (2021) reported that Inpari 39, Cakrabuana, Inpago 11, Rindang 1 and Luhur 1 have the potential to experience drought stress during the dry season on rainfed paddy fields with average productivity of 6 to 7 t ha -1 . Further, Cakrabuana has the highest grain yield around 7.15 t ha -1 when matured at 85 days after planting.…”
Section: Using Short-lived Paddy Varietiesmentioning
confidence: 99%
“…Mitigation management can be done by: 1) Use early maturing varieties and drought stress tolerance varieties. The use of early maturing to facing drought stress can be used to increase crop index (CI) and it will maintain high yields [158]. Drought tolerance varieties can respond and induces expression of drought stress related genes so that the plant will survive in these conditions [159].…”
Section: Drought Stress Managementmentioning
confidence: 99%
“…Climate change will decrease soybean production, especially due to rising temperatures in future climates, changing rainfall patterns, and unpredictable droughts/floods [8,9,10,11,6]. One of the ways for farmers to adapt to the impacts of climate change is by introducing new high-yielding, early maturing varieties, and drought-tolerant varieties [12]. One of the soybean varieties recommended for farmers' adaptation to climate change is the Biosoy soybean variety.…”
Section: Introductionmentioning
confidence: 99%